2015
DOI: 10.1002/term.2031
|View full text |Cite
|
Sign up to set email alerts
|

Treatment by Therapeutic Magnetic Resonance (TMR™) increases fibroblastic activity and keratinocyte differentiation in anin vitromodel of 3D artificial skin

Abstract: This study investigated the effect of extremely low-frequency pulsed electromagnetic fields (PEMFs) on skin wound healing in an in vitro dermal-like tissue. In this study, fibroblast and endothelial cells were utilized for the in vitro reconstruction of dermal-like tissues treated for various times up to 21 days with PEMFs. The effects of PEMFs on cell proliferation (MTT test), cell ageing (β-galactosidase test, ROS production), gene expression, the quality of the extracellular matrix and the amount of fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“… 25 For this purpose, we have already performed an in vitro study with dermal-like tissues to investigate the effects of TMR R magnetic fields on skin remodeling. 15 In the current study, we tested these PEMFs properties in vivo on consecutive Type-2 diabetic patients. After 15 days of treatment with TMR R , we investigated the ability of PEMFs to induce both proliferation and migration of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 For this purpose, we have already performed an in vitro study with dermal-like tissues to investigate the effects of TMR R magnetic fields on skin remodeling. 15 In the current study, we tested these PEMFs properties in vivo on consecutive Type-2 diabetic patients. After 15 days of treatment with TMR R , we investigated the ability of PEMFs to induce both proliferation and migration of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 Furthermore, in an i n vitro dermal-like tissue, we have previously demonstrated that TMR R enhances skin wound healing improving the quality of the extracellular matrix (ECM) and reducing ROS, leading to a positive rejuvenation effect on cells. 15 In the present work, we investigated, under clinical, cellular and molecular biology point of view, the influence of PEMFs on wound healing process in consecutive Type-2 diabetic patients, studying the granulation tissue of DFUs treated with TMR R .…”
Section: Introductionmentioning
confidence: 99%
“…Most reports found that ELF-EMFs could increase ROS levels, but there are also evidences indicated different results [ 67 , 68 , 72 , 73 , 74 , 75 , 86 , 88 ] ( Table 2 , Table 3 and Table 4 ). For example, it was shown that low intensity ELF-EMFs could reduce ROS levels in human keratinocytes, dermal fibroblasts [ 72 ] and neutrophils [ 76 ].…”
Section: The Effects Of Magnetic Fields On Rosmentioning
confidence: 99%
“…Most reports found that ELF-EMFs could increase ROS levels, but there are also evidences indicated different results [ 67 , 68 , 72 , 73 , 74 , 75 , 86 , 88 ] ( Table 2 , Table 3 and Table 4 ). For example, it was shown that low intensity ELF-EMFs could reduce ROS levels in human keratinocytes, dermal fibroblasts [ 72 ] and neutrophils [ 76 ]. In addition, ELF-EMFs could also decrease H 2 O 2 , cisplatin, oxygen-glucose deprivation (OGD), and hypoxia or hypoxia/reoxygenation (H/R)-induced ROS elevation in several cell lines [ 68 , 69 , 70 , 71 , 78 , 86 ] ( Table 2 ).…”
Section: The Effects Of Magnetic Fields On Rosmentioning
confidence: 99%
“…Their stimulation regime was actually quite complex, because they used 100 Hz PEMF pulses grouped in pulse packets, whose frequency was 2.89–25.9 Hz. Pulse packets were actually grouped in 0.3–2.8 Hz trains, which were in turn grouped into 0.1–0.3 Hz train sets [Ferroni et al, ]. It cannot be ruled out that different exposure conditions may be more effective on this cell model, as Yin et al [] stimulated human ADSCs with 1 mT, 50 Hz PEMFs for up to 21 days and reported a significant and very relevant increase in ALP and BGLAP expression, without mentioning the use of osteogenic medium.…”
Section: Effects Of Pemfs On Osteoblastsmentioning
confidence: 99%